Anthropogenic Impacts on Tropospheric Reactive Chlorine Since the Preindustrial. Issue 14 (22nd July 2021) - Zhai, Shuting; Wang, Xuan; McConnell, Joseph R.; Geng, Lei; Cole‐Dai, Jihong; Sigl, Michael; Chellman, Nathan; Sherwen, Tomás; Pound, Ryan; Fujita, Koji; Hattori, Shohei; Moch, Jonathan M.; et al.
Abstract: Tropospheric reactive gaseous chlorine (Cl y ) impacts the atmosphere's oxidation capacity with implications for chemically reduced gases such as methane. Here we use Greenland ice‐core records of chlorine, sodium, and acidity, and global model simulations to show how tropospheric Cl y has been impacted by anthropogenic emissions since the 1940s. We show that anthropogenic contribution of nonsea‐salt chlorine significantly influenced total chlorine and its trends after the 1940s. The modeled regional 170% Cl y increase from preindustrial to the 1970s was driven by acid displacement from sea‐salt‐aerosol, direct emission of hydrochloric acid (HCl) from combustion, and chemical reactions driven by anthropogenic nitrogen oxide (NO x ) emissions. Since the 1970s, the modeled 6% Cl y decrease was caused mainly by reduced anthropogenic HCl emissions from air pollution mitigation policies. Our findings suggest that anthropogenic emissions of acidic gases and their emission control strategies have substantial impacts on Cl y with implications for tropospheric oxidants, methane, and mercury. Plain Language Summary: Greenland ice cores preserve information from past atmospheres and provide information on how human activities have changed the composition of the atmosphere. While ice‐core chlorine mainly originates from deposited sea‐salt particles in the air, we found that emissions from human activities also influence ice‐core chlorine. Using six Greenland ice cores and global model simulations, we show that the observed increasing trend in nonsea‐salt chlorine during the 1940s–1970s was caused by enhanced human emissions of acidic gases and the resulting chemical reactions involving atmospheric sea‐salt particles, and the observed decrease after the 1970s is largely attributed to air pollution control strategies that are widely applied in North America and Europe. Key Points: Greenland ice‐core records showed nonsea‐salt chlorine increased from the 1940s to 1970s, and decreased leveled off afterward Historical simulations by a global model qualitatively capture the observed trends when only considering changes in anthropogenic emissions Modeled trends are driven by anthropogenic emissions of sulfur dioxide, nitrogen oxides, and coal combustion‐emitted hydrochloric acid